Effect of Pakkat Ethanol Extract (Calamus L. Blum) on Spermatogenesis and Testosterone Levels of Diabetes Mellitus Wistar Rats - Yolanda Eliza Putri Lubis; Anggi Sri Ananda Aipin; Hanjaya; Juliana Lina; Suhartomi (Postgraduate, University of Mataram, 2025)
Diabetes mellitus is a metabolic disorder marked by high blood glucose levels (hyperglycemia) that is caused by insulin deficiency. It also affects male infertility. Pakkat, young rattan, contains various phytochemicals, which can affect blood glucose levels, spermatogenesis, and testosterone production. Objective: To assess the effectiveness of Pakkat extract in regulating blood glucose levels, testosterone hormone, and spermatogenesis in alloxan-induced diabetic rats. This experimental study used 25 diabetic male Wistar rats and was grouped into five groups including negative control (distilled water), positive control (metformin), Treatment 1 (125 mg/KgBW Pakkat extract), 2 (250 mg/KgBW Pakkat extract), and 3 (500 mg/KgBW Pakkat extract) for 14 days. All data were analyzed by One-way ANOVA followed by a Post-Hoc Test. Pakkat extract at 125 mg/kgBW dose effectively reduced glucose levels (P-Value < 0.001) after 14 days. It also significantly increased spermatogenesis (P-Value < 0.001) and testosterone levels (P-Value < 0.001) in alloxan-induced diabetic rats. Thus, it can be concluded that any doses of Pakkat (Calamus L. Blume) extract significantly improve blood glucose levels after 14 days of administration. However, a higher dosage is required to increase spermatogenesis and testosterone hormone in diabetic conditions.